Determinants of IPO Underpricing: A Comparison between China and India - He, Xuyang (2018)
Initial public offering (hereby IPO) is an essential business activity in global capital markets, which represents an efficient way of financing for companies. During the IPO process, underpricing is a general phenomenon widespread in various countries. It is noticeable that China and India have significant IPO underpricing rate in decades, compared with developed countries such as US or UK. Classical and current literature in respect of IPO underpricing are reviewed in this study, and six main theories may have explaining power, which are signaling theory, underwriter reputation theory, winner’s curse theory, uncertainty theory, time-interval theory and industry-specific theory. 1941 IPO samples in China and 301 in India between 2007 to 2017 are selected, and regression models are used to test the relative importance of those main theories about IPO underpricing. China and India are tested separately and the results show that winner’s curse theory and signaling theory have the greatest impact to both countries, which is followed by uncertainty theory. Little influence of underwriter’s reputation can be seen in Chinese stock market, nevertheless, industry-specific theory may not explain IPO underpricing in India. In addition, time interval theory seems to have opposite explaining power in the two countries.